Effect of SiO2/EVA on the mechanical properties, permeability, and residual solvent of polypropylene packaging films. Issue 1 (1st August 2014) - Li, Dongli; Zhang, Jingyong; Xu, Wencai; Fu, Yabo
Abstract : The surface of nano‐silica was modified by ethylene/vinyl acetate (EVA) emulsion and then blended with polypropylene (PP) to yield a nano‐silica/PP composite material. This composite was intended to enhance the mechanical properties of PP, improve its melting point and degree of crystallinity, reduce its oxygen permeability and water vapor permeability, decrease the adsorption of PP packaging films against organic solvents, and improve the films' performance for food safety. The experiments showed that the crystallinity of PP modified by nano‐silica increased, leading to enhanced mechanical and barrier properties, while its melting point rose. Meanwhile, the residual solvent value of the modified PP films was reduced by 10–90%. POLYM. COMPOS., 101–107, 2016. © 2014 Society of Plastics Engineers